Identification of Soybean Genotypes for Pod Shattering Resistance Associated with Agronomical and Morphological Characters - Ayda Krisnawati; Mochammad Muchlish Adie (Biosaintifika: Journal of Biology & Biology Education, 2017)
A yield loss caused by pod shattering is one of the obstacles to the improvement of soybean productivity in tropical areas. The aim of this study was to identify the resistance of soybean genotypes to pod shattering as affected by agronomical and morphological characters. The field study was conducted in Malang, Indonesia, using 150 soybean genotypes. Data were collected on agronomical traits, the percentage of pod shattering, and pod morphological traits. Identification for shattering resistance was done as per oven dry method. Percentage of pod shattering was ranged from 0 % up to 100 % shattering with a mean of 58.11 %. Pod shattering was found to be negatively correlated with a number of pod per plant, the thickness of the pod, and Y/Z (seed weight and pod weight ratio). The Identification obtained 66 very highly susceptible genotypes, 19 susceptible genotypes, 19 moderate genotypes, 38 resistant genotypes, and 8 very resistant genotypes. Two of eight very resistant genotypes (G511H/Anj//Anj///Anj////Anj-6-11 and G511H/Anj//Anj///Anj////Anj-5-4) have high yield, medium maturity day and large seed size. Those lines could be used as gene donor for soybean varietal improvement for shattering resistance, and recommended to propose as new improved soybean varieties resistant to pod shattering in Indonesia.